Penerapan Material Requirement Planning (MRP) dengan Mempertimbangkan Lot Sizing dalam Pengendalian Bahan Baku pada PT. Phapros, Tbk. - Adelia Chandradevi; Nia Budi Puspitasari (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2016)
PT. Phapros Tbk is one of the oldest and biggest pharmaceutical company in Indonesia. As raw material inventory plays a key role to compete in this type of industry, it is important for PT. Phapros, Tbk to keep it well maintained. However, the Production Planning and Inventory Control Division, whose responsibility is planning and controlling the raw material has not implemented the Material Requirement Planning (MRP) method that causes a problem regarding the overstock of captopril, the ingredient for producing captopril 25 mg tablet. There are too much raw materials ordered and ends up with higher expense. The author proposed a lotting method to develop an efficient raw material planning. Results shows that using Wagner Within Algorithm method can help the company minimizes the total expense spent by Rp 984.977.